Surveillance of suicide deaths involving gases in Australia using the National Coronial Information System, 2006 to 2017 - Alexander C.R. Burnett; Nicola A. Chen; Lauren McGillivray; Mark E. Larsen; Michelle Torok (Elsevier, 2021)
Abstract Background: There have been concerns about the increased use of helium and nitrogen gas as a suicide mechanism in Australia. Methods: National Coronial Information System data were used to investigate gas‐specific suicides in Australia over the period 2006-2017. Characteristics were compared between helium or nitrogen, carbon monoxide and seven other gases. Results: Gas inhalation accounted for 10% (3,103/31,002) of all suicide deaths in Australia between 2006 and 2017. The mean age of individuals who died by suicide was 47.6 years (SD 16.9, R 14‐97) and 83.3% were male. The number of gas suicides declined over the study period (IRR=0.96). The fall was associated with a 47% decline in carbon monoxide suicides (IRR=0.93). There was an increase in deaths due to argon (IRR=1.60) and nitrogen (IRR=1.27). Compared to individuals using other non‐carbon monoxide gases, individuals who died by suicide from helium or nitrogen were significantly more likely to be older, have a physical illness and/or disability, have contacted a euthanasia group and have accessed instructional material and purchased gas online. Conclusions: Suicides by carbon monoxide decreased between 2006 and 2017 alongside an increase in argon and nitrogen gas use - particularly among older adults. The ease of access to these gases points to new targets for means restriction. Implications for public health: Identifying the types of gases used in suicide deaths and emerging trends may enable targeted interventions that could potentially reduce access.